Right dislocation as ellipsis: The Copula kān in Jordanian Arabic - Tariq Farghal,; Nisreen Al-Khawaldeh,; Yazan Al-Mahameed, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study investigates the syntactic phenomenon of verbal right dislocation of the copula kān (be PAST) in Jordanian Arabic. Based on Kayne’s Axiom, phrasal categories (XPs) across languages are moved to the left periphery while any movement toward the right periphery must be perceived ‘anti-symmetrically’ as preceding the head. However, Jordanian vernacular seems to enable XPs as well as copular verbs to be right dislocated. Following Ott and Vries’s analysis in Dutch and German, this dislocation appears to be elliptical where the copula is moved out of the elided clause and has a semantically asymmetrical unitary relationship with the host. This assumption is supported by various tests including agreement, clausal distinction, and insertion of adverbs and models, which affirms that Right Dislocation is ellipsis-based rather than movement-based. This study delves into an unexplored area of Arabic syntax of dislocation including nominal dislocation as well as verbal dislocation of Arabic copular forms. By gathering syntactic judgments of Bachelor’s English students at Amman Arab University, the study reveals through minimal contrast examinations in various syntactic contexts the evidentiality of ellipsis in Arabic right dislocation, contributing to the knowledge of the syntax of the Jordanian L variety and offering insights into descriptive grammar.